Birth order, daycare attendance, and childhood socioeconomic status in relation to gingivitis: a cross-sectional study in Turkish young adults - Zeynep Tastan Eroglu; Dilek Ozkan Sen; Osman Babayigit; Kaan Yildiz (BMC Oral Health)
Abstract Aim Birth order, sibship size, breastfeeding, daycare attendance, and delivery method are known to influence the development of gut microbiota and the immune system, affecting the risk of many infectious diseases. This study aims to explore the impact of these factors, along with socioeconomic background and familial factors, on gingivitis and oral hygiene practices in early adulthood among the Turkish population. Materials and methods Patients were diagnosed using periodontal clinical and radiographic assessments, adhering to the 2017 World Workshop on the Classification of Periodontal and Peri-Implant Diseases and Conditions. The study included 18-year-old individuals diagnosed with either generalized gingivitis or clinical gingival health. Data collected included sociodemographic factors, birth order, sibship size, delivery methods, breastfeeding duration, daycare attendance, and oral hygiene behaviors. Binary logistic regression was employed to analyze the associations between these factors and the presence of generalized gingivitis. Results A total of 178 individuals were evaluated, including 124 with generalized gingivitis and 54 with clinical gingival health. Daycare attendance was significantly associated with gingival health. Among those with gingival health, 55.6% had attended daycare, whereas only 29% of participants with generalized gingivitis had attended daycare. Conversely, 71% of those with generalized gingivitis did not attend daycare, compared to 44.4% in the gingival health group (p = 0.001). Univariate logistic regression identified a significant association between daycare attendance and a reduced risk of generalized gingivitis (Odds Ratio [OR] = 0.327, p = 0.001). Later birth order was associated with a reduced risk of gingivitis (OR = 0.470, p = 0.037). Sibship size, delivery methods, and breastfeeding duration showed no clear associations with gingivitis (p > 0.05). Conclusions The findings indicate a potential association between oral health status in adulthood and early childhood exposures, such as daycare attendance and birth order. Further research is necessary to confirm these associations and elucidate the mechanisms involved, even though these factors may contribute to gingival health in early adulthood. These insights may enhance our understanding of how early-life exposures relate to oral health outcomes and suggest that considering such factors could be beneficial in future oral health management strategies. Trial registration Trial registration is also available at clinicaltrail.gov. Clinical Trials-ID: NCT06240247. Registration Date: 22.01.2024.